2022
DOI: 10.1128/spectrum.02495-22
|View full text |Cite
|
Sign up to set email alerts
|

Host-Mediated Copper Stress Is Not Protective against Streptococcus pneumoniae D39 Infection

Abstract: Streptococcus pneumoniae (the pneumococcus) is one of the world’s foremost bacterial pathogens. Treatment of both localized and systemic pneumococcal infection is becoming complicated by increasing rates of multidrug resistance globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Further work revealed that StP and the Cnt importer enable Cu to gain access to the bacterial cytoplasm, and that import via this transporter can overwhelm the Cu detoxification machinery. A recent study revealed that during infection, Cu abundance increases ~150-fold in Zn-depleted regions of tissue 38 . This leads to a model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further work revealed that StP and the Cnt importer enable Cu to gain access to the bacterial cytoplasm, and that import via this transporter can overwhelm the Cu detoxification machinery. A recent study revealed that during infection, Cu abundance increases ~150-fold in Zn-depleted regions of tissue 38 . This leads to a model (Fig.…”
Section: Discussionmentioning
confidence: 99%